If you're a kid like Gavin - Grimm, Gavin; Lukoff, Kyle (Katherine Tegen Books, 2022)
As a young child, Gavin Grimm makes the choice to be honest with his family and tell them he's really a boy. But after Gavin starts high school, he isn't given much choice on where to use the bathroom because girls are expected to use the girls' bathroom and boys are expected to use the boys' bathroom. Since Gavin is a boy, he knows where he should go, but not everyone agrees with him. Eventually, a meeting is called to discusses the issue, and Gavin makes a choice to speak up for himself. He begins sharing his story on the news and begins working with the ACLU to bring his case before the Supreme Court. Includes an author's note.